2018
DOI: 10.1002/jsfa.8962
|View full text |Cite
|
Sign up to set email alerts
|

A novel, simple, economic and effective method for retarding maize tortilla staling

Abstract: This work showed that GMF can play the role of a self-hydrocolloid anti-staling agent by retarding the retrogradation of maize starch and deterring the loss of water and rheological properties of masa and the increase in undesirable sensory characteristics of tortilla such as increased firmness. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…That means that in tortillas with PA there was less retrogradation, which can be explained due to the interaction between PA and gelatinised starch which formed amylose‐lipid complexes. In contrast samples without PA presented a higher ratio value, which implies that this samples have more crystalline structures related to a higher degree of amylopectin retrogradation, as reported by other authors (Alvarez‐Ramirez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…That means that in tortillas with PA there was less retrogradation, which can be explained due to the interaction between PA and gelatinised starch which formed amylose‐lipid complexes. In contrast samples without PA presented a higher ratio value, which implies that this samples have more crystalline structures related to a higher degree of amylopectin retrogradation, as reported by other authors (Alvarez‐Ramirez et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The most recurrent is the use of hydrocolloids, such as carboxymetyl cellulose, guar gum, xanthan gum, arabic gum, and Hymenaea courbaril gum (Rendón‐Villalobos et al ., ; Román‐Brito et al ., ; Lucius et al ., ; Calderón‐Peralta et al ., ). Hydrocolloids act as retrogradation retarding agents is that these components interact strongly with amylose and amylopectin chains through H bonds forming robust 3D networks with good water‐holding capacity, which decrease the interaction between the amylose and/or amylopectin chains delaying the aggregation and recrystallization of starch (Alvarez‐Ramirez et al ., ). Recently the use of a gelatinized maize flour dispersion also was proved to act as hydrocolloid reducing starch retrogradation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The xanthan gum decreased water loss and increased starch gelatinization, avoiding retention of starch crystal nuclei that facilitated starch retrogradation. This change in tortilla quality is related with staling that has been commonly attributed to recrystallization of starch chains (Alvarez‐Ramírez, García‐Diaz, Vernon‐Carter, & Bello‐Pérez, ). Soybean bagasse addition appears to have played an antistaling role by diluting starch (Figure b) and retrogradation.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these correlations, it was concluded that lower content of pregelatinized starch (high C3) in NMF samples led to higher retrogradation (high C5). Alvarez‐Ramirez et al () found that adding completely gelatinized NMF retarded starch retrogradation. According to these authors, the gelatinized starch acts as self‐hydrocolloid due to its binding water capacity.…”
Section: Resultsmentioning
confidence: 99%